A time saving ZnO nanoparticle fabrication approach for bulk photocatalytic applications. (2021) - Sharma, Ramesh K.; Ankita,; Singh, Rajender; Kumar, Anil; Goyal, Navdeep
Abstract: Instant synthesis of Zinc Oxide (ZnO) nanostructures has been reported here by simple mixing of zinc precursor with sodium hydroxide base at pH = 7. This method can be useful for treating bulk effluents saving time and cost. In order to make comparative study at same pH, ZnO nanostructure has been prepared by conventional mixing method also. Crystal purity of ZnO nanostructure has been verified with X-ray diffraction technique whereas morphological information is studied with Field Emission Electron Microscope. Optical properties are invesigated with help of UV–vis spectroscopy. Prepared samples are investigated as photo catalyst for Methylene Blue (MB) dye degradation using natural sunlight. The 95% & 70% dye degradation values have been observed for instant and conventional method respectively. Novelty of reported instant synthesis over conventional techniques is that it has minimum preparation time, high yield for bulk production and cost effectiveness due to minimum use of apparatus and reusability of catalyst due to larger particle size. This study really has features like economical, effectiveness as well novelty in approach.